Towards parenthood : preparing for the changes and challenges of a new baby - Milgrom, Jeannette (ACER Press, 2009)
Towards Parenthood aims to assist soon-to-be and current parents manage the complex demands of parenting and strengthen the parent-infant relationship and the couple relationship. The book covers expectations of parenthood, skills in coping, problem-solving, enhancing self-esteem, assertive communication, bonding with your baby and understanding your baby's cues.